A multi-layer architecture for high available Enterprise JavaBeans - Pasin, Marcia; Weber, Taisy Silva; Riveill, Michel (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2002: Anais do III Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2002.23403, 2002)
EJB (Enterprise JavaBeans) spec does not describe high availability as one of its properties. If the application server fails, the service remains unavailable while it recovers. Some EJB server vendors claim to provide this desirable property implementing server replicas through centralized protocols. Unfortunately, these protocols could lead to an unavailable service if the coordinator server crashes. We are presenting a new architecture aiming high available EJB servers based on distributed concepts. Our replicas are modeled as state machines synchronized by group communication primitives. We achieve high availability to EJB application servers running stateful and stateless session beans.